(untitled) (Al-Qamar, 2020)
Allah almighty has given a special privilege to man from his creatures, in the form of appearance, the most beautiful and the most beneficial in knowledge, it has been made the universe of the universe, one aspect of this honor is that all the universe is served for its diet or medicine, and many things have been lawful for its diet or medicine, and the other aspect is that human organs are prohibited for medicine and their purchase Has been declared invalid. In the eyes of Islam, human life is indeed a trustworthy one, which is a serious crime to destroy, big goods have been prepared to protect it, and such possible measures have been made necessary to save human life, which is the worst crime in the eyes of Islam. Similarly, the person who is starving is allowed to say the word "" disbelief" ". However, in this situation, in order to save life, respect for humanity has not been allowed to destroy any other human being or organ.